Propuesta de un plan para la implementación de un sistema integrado de gestión basado en las normas NTC ISO 9001, 14001 para una empresa de combustibles industriales (2018)
The present degree work was carried out with the purpose of developing an implementation plan for an Integrated Management System of the ISO 9001: 2015 and ISO 14001: 2015 standards for an organization dedicated to the collection, transport and final disposal of waste and fuels. A main diagnosis was made of the organization to determine the gaps in terms of compliance with requirements in each of the processes of the same, based on the high-level structure to respond to the needs of the company to establish an improvement.